Development of Google Sites -Based Sports and Healty Physical Education E-Modules For Class 4 Students Of Ash Shiddiqi SDIT Jambi city - Riqky Ananda Putra; Sofyan Sofyan; Ilham Ilham (Universitas Muhammadiyah Enrekang, 2024)
The Revolutionary Era of Industry 5.0 brings significant impacts on human life, especially in the field of education (Oktarina et al., 2021; Razak et al., 2021). Education is crucial for individuals from childhood to adulthood (Yulius et al., 2022; Dahlan & Arini, 2022). In this era, technology is widely utilized to support various aspects of work (Mood & Mahayukti, 2013; Fradila et al., 2021; Misra, 2012). Education serves as a fundamental platform for shaping character and intellectual development. With continuous technological advancements, education faces challenges in adapting to these changes. The integration of technology in learning has created new opportunities for delivering engaging, interactive, and effective learning materials. One recent innovation is the Smart Classroom, which merges advanced digital learning technology with traditional teaching methods. Physical education is an essential component of the education system, aimed at promoting health, fitness, and physical skills. It also plays a role in developing a healthy lifestyle, social interaction, and awareness of physical well-being. The use of digital media enhances the learning process in physical education by increasing students’ interest and talent. In Indonesia, traditional teaching methods like lectures dominate physical education, which are often considered uninteresting. Introducing innovative learning methods and media, such as e-modules and digital platforms like Google Sites, can significantly improve the quality of physical education. This study focuses on developing a Google Sites-based e-module for 4th-grade students at SDIT Ash-Shiddiiqi Jambi City, aiming to enhance the effectiveness of the Smart Classroom program and increase student engagement and understanding in Physical Education, Sports, and Health (PJOK).